Entrepreneurial Culture dan Kinerja Usaha Kecil: Peran Mediasi Entrepreneurial Competence - Endi Sarwoko; Iva Nurdiana Nurfarida (Jurnal Manajemen dan Kewirausahaan, 2021)
The purpose of this study is to broaden the resource-based view by examining the effects of entrepreneurial culture on SMEs performance, and to analyze the role of entrepreneurial competence in mediating the effects of entrepreneurial culture on business performance. The study used a quantitative approach, carried out on tourism-supporting SME companies in Batu City. Collecting data using a questionnaire with a sample of 117 SMEs selected randomly. The analysis technique uses PLS-SEM to test the hypothesis. Research findings reveal that business performance in SMEs will be determined by the entrepreneurial culture and entrepreneurial competence of the owners/managers. Entrepreneurial competence can be achieved if the owners/managers have a strong entrepreneurial culture. Research confirms the resource-based view that entrepreneurial competence as a superior resource will provide a competitive advantage, so that it plays a role in achieving business performance. It is important for SMEs to strengthen the entrepreneurial culture in order to achieve business performance, because the entrepreneurial culture will direct the behavior of owners/managers to improve their competencies, which will realize business performance. More extensive research is needed to improve the level of generalization, in addition, further researchers consider the role of dynamic capability in relation to competence and business performance.